Optimization of Online Pharmacy System to Lower the Late Billing for Chronic Disease Drugs - Herwendanasari, Deltania; Andarini, Sri; Zuhriyah, Lilik (Fakultas Kedokteran Universitas Brawijaya, 2022)
One of the biggest cost control problems among hospitals in the National Health Insurance is chronic disease drug services. Billing fee delays or unpaid billing fees often occur due to patient failure to revisit the doctor according to the requirement of 30 (thirty) days from the last visit. It resulted in the hospital's inability to collect the financing for chronic disease drugs from Social Security Administrative Agency (BPJS). This study aimed to discover the root cause of the pending billing of chronic disease drug costs and executable solutions in hospitals. This research was conducted at X Hospital Malang. This research used mix-method of qualitative and quantitative. The qualitative method were observations of the service flow for chronic disease patients, interviews with all unit coordinators, and focus group discussion with the Pharmacy Unit and Casemix Unit coordinators. The quantitative method was done using CARL scoring to determine the priority of the problem solution. The root of the problem was the lack of adequate systems and resources in chronic disease drug services. The possible solution is to modify the flow in the outpatient pharmacy. It is necessary to apply patient screening through the Online Pharmacy Application at the outpatient pharmacy to prevent patients who visit for less than 30 days. The results of the solution implementation are expected to reduce the amount of money from pending billing for chronic disease drug costs, thereby minimizing hospital financial losses.